PENGARUH PENGGUNAAN BEBERAPA MACAM PUPUK SUSULAN DAN BATUAN FOSFAT TERHADAP PERTUMBUHAN DAN HASIL KUBIS BUNGA PADA INCEPTISOL - , Nilla Kristina, Prof. Dr. Ir. Djoko Prajitno, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Using nature materials for sources of nutrients in cultivation of cauliflower can be alternative fertilization for cauliflower that more environmentally friendly, easily available, and more economically advantageous. The aimed of this research wasto find best combination between advanced fertilizer and dosage of rock phosphate for increasing growth and yield of the crop and also increase economic efficiency of rock phosphate for cauliflower cultivation in Inceptisol. This research was done in Tiagan Pakan Sinayan, Bukittinggi City, from Desember 2010 until April 2011. The research was factorial treatments 3 x 3 and one treatment as a control that arranged by using Randomized Completely Block Design (RCBD) in three replications. The first factor was advanced fertilizer consisted of 3 levels : liquid fertilizer of goat urine, liquid fertilizer of goat urine feses and liquid fertilizer of Tithonia diversifolia compost. The second was rock phosphate dosage consisted of 3 levels : 0, 1000, 2000 kg/ha. The control was not using advanced fertilizer and rock phosphate. The result showed that advanced fertilizer and rock phosphate interacted each other affecting the growth of crop. In generally, cauliflower that given urine feses showed higher growth at all of rock phosphate dosage level. Urine feses at 2000 kg/ha rock phosphate treatment showed better growth than urine and Tithonia diversifolia at the same level, except for leaf area index at the harvest time. Tithonia diversifolia showed the best leaf area index at the harvest time. Tithonia diversifolia at 2000 kg/ha rock phosphate treatment give best diameter of curd compared to the other treatments combination, although not significant different to urine feses at 2000 kg/ha. The yield/plant and yield/ha is not significant different at all of treatments combination. Tithonia diversifolia and urine feses at 1000 kg/ha rock phosphate gave best economic advantage for cauliflower cultivation in Inceptisol.